Burden of disease using disability adjusted life years in the Middle East and North Africa (MENA) region: protocol of a systematic review - Linda Östlundh; Michal Grivna; Rami H Al-Rifai; Brecht Devleesschauwer; Balazs Adam; Moustafa Sherif; Simy Mathew (BMJ Open, 2025)
Introduction In the Middle East and North Africa (MENA) region, changing demographic and epidemiological profiles have resulted in a diverse and shifting burden of disease (BoD). Disability-adjusted life years (DALYs), which combine years of life lost (YLL) due to premature mortality and years lived with disability (YLD), offer a valuable metric for assessing disease burden at the national level. While global burden of disease (GBD) estimates provide broad insights, national burden of disease (NBD) estimates offer country-specific data that can better inform tailored health policies and resource allocation. This systematic review protocol outlines our methodology for collating and analysing the NBD estimates in the MENA region using DALYs as the primary outcome measure.Methods and analysis This review will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We will systematically search PubMed, Scopus, Web of Science and EMBASE for studies published from 1993 to 2024 that report national-level DALY estimates for diseases, injuries or risk factors in MENA countries. Eligible studies must report DALY estimates using national methodologies, while studies using exclusively GBD estimates will be excluded. Two independent reviewers will conduct title/abstract and full-text screening, data extraction and quality assessment using Standardised Reporting of Burden of Disease Studies (STROBOD), with disagreements resolved by a third reviewer when necessary.Ethics and dissemination Ethical approval is not required for this review as it involves analysis of previously published data. The findings will be disseminated through publication in a peer-reviewed journal and presented at relevant academic and policy forums.Prospero Registration Number PROSPERO CRD42024498688.